2010
DOI: 10.4050/jahs.55.032001
|View full text |Cite
|
Sign up to set email alerts
|

Wind Tunnel and Flight Evaluation of Passive Stabilization of a Cargo Container Slung Load

Abstract: In forward flight helicopters carrying slung loads frequently encounter load instability problems that reduce their speed envelope to well below the power limit of the helicopter/slung-load system. The paper presents a procedure for the development and flight test verification of passive stabilizers designed to increase the maximum flight speed of the system. Most of the development is carried out during wind tunnel tests. A scale model is suspended from the tunnel ceiling by a gimbaled setup that simulates th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 14 publications
0
29
0
Order By: Relevance
“…Initial tests indicated that the dynamic behavior of the wind tunnel model is not sensitive to these details (Ref. 3). Thus, the wind tunnel model was a simple box without corrugations, indented corners, or skids.…”
Section: General Description Of the Testsmentioning
confidence: 99%
See 4 more Smart Citations
“…Initial tests indicated that the dynamic behavior of the wind tunnel model is not sensitive to these details (Ref. 3). Thus, the wind tunnel model was a simple box without corrugations, indented corners, or skids.…”
Section: General Description Of the Testsmentioning
confidence: 99%
“…3) that PIO played a role in the system dynamics at airspeeds where the system was marginally stable. Thus, at those flight speeds, after the pilot introduced a lateral excitation, two modes of the system response were studied: a "lateral stick fixed" (SF) mode and a mode where the pilot remained active in the lateral loop (denoted as "pilot in the loop" (PIL)) and tried to minimize the helicopter roll oscillations.…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations